A History of Maritime Radio-Navigation Positioning Systems used in Poland. (11th January 2016) - Specht, Cezary; Weintrit, Adam; Specht, Mariusz
Abstract : This paper describes the genesis, the principle of operation and characteristics of selected radio-navigation positioning systems, which in addition to terrestrial methods formed a system of navigational marking constituting the primary method for determining the location in the sea areas of Poland in the years 1948–2000, and sometimes even later. The major ones are: maritime circular radiobeacons (RC), Decca-Navigator System (DNS) and Differential GPS (DGPS), as well as solutions forgotten today: AD-2 and SYLEDIS. In this paper, due to its limited volume, the authors have omitted the description of the solutions used by the Polish Navy (RYM, BRAS, JEMIOŁUSZKA, TSIKADA) and the global or continental systems (TRANSIT, GPS, GLONASS, OMEGA, EGNOS, LORAN, CONSOL) - described widely in world literature.